(untitled) (Journal of Pharmaceutical Negative Results, 2023)
Vasa previa, a rare pathology seen in obstetrics may endanger the fetus's life because of its high likelihood of bleeding. Although the appearance of cord blood vessels is a very uncommon clinical condition, it is dangerous for the fetus or the infant since it is linked to a higher risk of perinatal death. To enhance the perinatal outcome, focused screening with ultrasound for vasa previa should be performed in women with high-risk factors. Ultrasound is the choice of investigation for the detection of vasa previa. We report a case of bleeding vasa previa at 37 weeks of gestation in a 29-year-old woman. This article aims to improve perinatal outcomes in these situations and to have a high index of suspicion for the diagnosis of vasa previa when presented with antepartum hemorrhage with a history of a low-lying placenta.